(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
This paper deals with terrestrial, freshwater and marine molluscs collected in the upper Pleistocene deposits of clay, sands and gravels of S. Teodoro Cave (North-eastern Sicily). Beginning from 1998 two trenches have been excavated (1998 and 2002-2004). A highly diversified assemblage of endemic and not endemic vertebrates (elephant, horse, wild ox, deer, wild boar, hyaena, fox, mouse, ground vole, shrew, hedgehog, bats, birds, reptiles), invertebrates (molluscs) and vegetal remains have been collected from the two trenches. The molluscan fauna is represented by poor to rich-species assemblages of land and freshwater gastropods and bivalves with Mediterranean-European character. Some species have been found for the first time as fossils in Sicily. The land snails prevail in the 1998 trench showing a persistent arid environment during the time of the sediment deposition. The freshwater species, characteristic of slow-running water, point to the presence of a small water body (stream or spring) inside the cave, probably more consistent in the 2002-2004 trench where this fauna prevails. The dispersal of the molluscan fauna of S. Teodoro Cave from the mainland during the low stand sea-level phases of the upper Pleistocene probably belongs to the same dispersal events following the Oxygen Isotope Stage 5e which introduced into the island not endemic faunal elements which are associated with endemic faunal elements in S. Teodoro Cave. Littoral marine reworked molluscs found in the cave deposits probably come from the sedimentary cover of a middle Pleistocene terrace which overlies the roof of the cave. SHORT NOTE